Ethnobotanical study of medicinal plants used to treat microbial infections in the Fez-Meknes region, Morocco - Yassara, Soufyane; Jaouhar, Samira; Zeouk, Ikrame; Bekhti, Khadija (Ethnobotany Research and Applications, 2025)
Background: The Moroccan community is well-known for using medicinal and aromatic plants (MAPs) to treat a variety of illnesses. The purpose of this work is to investigate the use of MAPs in the Fez-Meknes region, located in central-northern Morocco. Methods: An ethnobotanical survey (January–March 2023) interviewed 300 respondents to document the use of MAPs in the treatment of diseases of microbial origin. Data were analyzed using citation indices such as Relative Frequency of Citation (RFC), Family Importance Value (FIV), Plant Part Value (PPV), and Fidelity Level (FL) and Factorial Correspondence Analysis (FCA) performed by PAST software to link socio-demographic factors (age, gender, education, and socio-economic level) with plant use. Results: Among the people interviewed, 90.66% use MAPs. For the treatment of infectious diseases, 68 plant species belonging to 32 families (Lamiaceae, Myrtaceae, Apiaceae, etc.) have been recommended, including Rosmarinus officinalis, Thymus atlanticus, Chamaemelum nobile, etc. These plants are frequently prepared by decoction. The categories of people most likely to use MAPs are women, the elderly, people with low or average incomes, and those who are illiterate or have only primary schooling. Conclusions: The current study emphasized the widespread usage of MAPs as traditional treatments among the people surveyed in the Fez-Meknes area. As a result, this effort will provide researchers access to a valuable ethnobotanical database that they may use to further pharmaceutical knowledge. In addition, the species identified could constitute a promising resource of new natural antimicrobial agents, offering interesting opportunities in the fight against antibiotic resistance. Keywords: Ethnobotanical study, Medicinal and aromatic plants, Traditional medicine, Phytotherapy, Infectious diseases, Fez-Meknes